The Violation of Campaign Props Installation in 2019 Election in Pekanbaru - Adrian Faridhi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2020)
The holding of the 2019 Election is a historic event for the Indonesian Nation, because it is the first election that combines the Election of President and Vice President with the Legislative Election. Law Number 7 of 2017 concerning General Elections regulates the Campaign mechanism, one of which relates to the use of Campaign Props, yet the regulation in its implementation still violates the use of campaign props. With the interest of investigating this problem, this study used the research methodology in the form of sociological juridical research on primary data collected from field research. The results of this study showed the campaign props that violate the provisions of the legislation derived from installation, and some props are still installed even though the campaign period has finished. The solution of this research is advocating the need for close supervision of the installation of campaign props and outreach for election participants and the winning team not to violate the provisions of the election law.